MAINSTREAMING ISU DISABILITAS DI MASYARAKAT DALAM KEGIATAN PENELITIAN MAUPUN PENGABDIAN MASYARAKAT DI STAIN KUDUS - Ningsih, Ekawati Rahayu (Jurnal Penelitian, 2014)
MAINSTREAMING DISABILITIES ISSUE IN THE COMMUNITY IN REASEARCH ACTIVITIES AND COMMUNITY SERVICES IN STAIN KUDUS. This paper aims to build important issues surrounding the services and facilities development for disabled people, especially in college. In the last three decades, the process of change and a shift in meaning and disability paradigm in both the national and international realm, capable of carrying a significant impact on policy direction and agenda of disable movement (disability movement) as well as academic studies which support it. This is important, because people with disabilities should have the same role and the opportunity to explore their potential, particularly in higher education and work. However, disabled people only have a much lower participation rate than non-disabled, amounting to 0.01 percent. While the government’s policy on inclusive education has not been understood and implemented properly due to various reasons. So that these conditions further aggravate the disabled to be able to develop optimally as befits a normal human being. Therefore, this study was conducted in an effort to maximize services for disabled people, especially in the STAIN Kudus.